2018
DOI: 10.1111/fcsr.12272
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Consumption by Age of Single‐Person Households in Korea

Abstract: This study analyzed the electricity consumption of single‐person households in Korea and examined whether the determinants of electricity consumption varied by age. The study analyzed the physical characteristics, demographic and economic characteristics, and electricity consumption characteristics. The sample included 1,035 single‐person households; it was drawn from the 2014 Korea Energy Consumption Survey. Descriptive statistics revealed differences in most characteristics by age. The results of multiple re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…This result is not consistent with a study by Yohanis who found that people aged 65 and above consumed electricity more than younger people [37]. However, Kim [20] who studied electricity consumption behavior of singleperson households, claimed that the average electricity use by age group is the highest in their 30s, and the higher the age group, the lower the electricity consumption. As shown in Figure 4, the minimum value of the average number of household members is 2.01 (Gwanak-gu), the maximum value is 2.69 (Yangcheon-gu), and the average number of household members in each autonomous district in Seoul is less than 3.…”
Section: Correlation Analysis Between Electricity Consumption and Agecontrasting
confidence: 89%
See 1 more Smart Citation
“…This result is not consistent with a study by Yohanis who found that people aged 65 and above consumed electricity more than younger people [37]. However, Kim [20] who studied electricity consumption behavior of singleperson households, claimed that the average electricity use by age group is the highest in their 30s, and the higher the age group, the lower the electricity consumption. As shown in Figure 4, the minimum value of the average number of household members is 2.01 (Gwanak-gu), the maximum value is 2.69 (Yangcheon-gu), and the average number of household members in each autonomous district in Seoul is less than 3.…”
Section: Correlation Analysis Between Electricity Consumption and Agecontrasting
confidence: 89%
“…In particular, the average monthly income tended to decrease as individuals aged. The lowest-income individuals among the single-person households were in their 60s or above [20]. Therefore, since it is estimated that the share of electricity costs among the average monthly income for single elderly households is considered to be high, it is necessary to resolve this issue by lowering the requirements of the National Basic Living Security for single-person elderly households.…”
Section: Introductionmentioning
confidence: 99%
“…The findings begin addressing social research gaps exploring relationships among sociodemographic characteristics, particularly age, awareness, and behaviours influencing home energy consumption [5,7] and supports fiscal energy analyses of residential electricity usage showing the relevance of age [1][2][3][4]6]. Specifically, it contributes an Australian sample to international studies noting older individuals are more likely to consider environmental impacts of energy consumption [9,7].…”
Section: Resultssupporting
confidence: 57%
“…This paper presents social survey findings about environmental sustainability knowledge and home energy usage decisions displayed by individuals at an Australian university. A growing body of international energy research shows household income, family composition, community type, and other demographics predict household energy consumption, with most using consumer economics frameworks to investigate appliance usage rates [1][2][3][4][5][6][7][8]. Although government energy policies broadly note the environmental benefit of reducing energy consumption, conceptual frameworks focus on socioeconomic investigations of energy consumption, with most exploring how the socialisation processes affects youth and other family members' modification of household energy practices [5,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Kim (2018) examined energy consumption of single‐person households in Korea using the 2104 Energy Consumption Survey. She found that low‐income elderly homeowners were big users of electricity in the winter.…”
Section: Discussion Of Resultsmentioning
confidence: 99%